Avaliação de acibenzolar-s-metil, extrato cítrico e fermentado bacteriano no controle da murcha-bacteriana (Ralstonia solanacearum) do tomateiro (Lycopersicon esculentum Mill) - Costa, Viviane Carla (2007)
The bacterial wilt caused by Ralstonia solanacearum is one of the main diseases that can reduce the productivity of tomato culture (Lycopersicon esculentum). The control of this pathogen is difficult, since the bacteria overwinter in plant debris, in diseased plants and in the soil. The use of resistance varieties is difficult because it depends on environmental conditions and amount of bacteria in the soil. Thus, it is necessary the development of alternative methods for the control of this disease, since there is no registered pesticide for this purpose. The objective of this work was to verify the effectiveness of the acibenzolar-S-methyl (ASM) abiotic product, and citric biomass and bacterial fermented extract biotic products in inducing resistance in the tomato against R. solanacearum biovars I and III. To in vitro assay the ASM was used at concentrations of 10, 25, 100 and 200 mg/L, while citric biomass and bacterial fermented extract were used at concentrations of 0.025, 0.1, 0.2 and 0.4 mL/L. Oxytetracycline (22.5 mg/L) + streptomycin (225 mg/L) was used as positive control and only culture medium as negative control. To in vivo assay the doses were 0.05 g/L for ASM, 2.5 and 5 mL/L for citric biomass and 10 and 20 mL/L bacterial fermented extract. After 15 days of transplanting the products were sprayed on the leaves, with a total of 10 applications. Three days after the first application the plants were inoculated with the pathogen through wounds in the roots. The results showed that the three products presented antibacterial activity against R. solanacearum, with differentiated action depend on the dose and biovar inoculated. For ASM the inhibition was of up to 99%, whereas for citric biomass and bacterial fermented extract it was 84% and 99%, respectively. The antibiotic inhibited between 7.5 and 15% the bacterium growth. To in vivo assay, the citric biomass 5 mL/L and bacterial fermented extract 10 mL/L reduced the bacterial wilt caused by biovar I of R. solanacearum, whereas to biovar III the control was obtained with bacterial fermented extract (10 mL/L) and ASM. In these plants with low incidence of wilt symptoms were observed the lower indexes of bacterium isolation in culture medium. These results indicate the potential of ASM, citric biomass and bacterial fermented extract for control of R. solanacearum in tomato plants